(untitled) (Medico Legal Update, 2021)
Introduction: Euthanasia is considered to be contradictory to the 1945 Constitution of the Republic of Indonesia, which is contained in Chapter XA, second amendment about human rights which are concerning about the right to live and the right to be protected. There are no specific laws and regulations which regulate Euthanasia in Indonesia; therefore, it is important to research the laws and regulations that have to possibility to regulate Euthanasia, especially in the Indonesian criminal law system at present time. Purpose of Research: This research aims to acknowledge and analyze the Euthanasia criminal action formulation policy in the criminal law system at present time. Research Methodology: This research is a normative juridical legal research with a statute approach. Discussion: The practice of Euthanasia is prohibited by Article 344 of the Criminal Code; therefore, the regulations must be based on the court order, either the active Euthanasia which is stated real and sincere by the victim or the passive Euthanasia which is stated by other parties other than the victim.